2018
DOI: 10.3390/healthcare6020056
|View full text |Cite
|
Sign up to set email alerts
|

Chief Nursing Officers’ Views on Meeting the Needs of the Professional Nurse: How This Can Affect Patient Outcomes

Abstract: Chief Nursing Officers (CNOs) have a demanding, complex role that commands accountability in leading the nursing profession and achieving quality patient outcomes. The purpose of this study was to understand the CNO’s view of meeting the needs of the Registered Nurse (RN) at point of care and how this could affect quality patient outcomes. In two qualitative studies twenty-five CNOs were individually interviewed in eight states including: Florida, Tennessee, Kentucky, Maine, New Hampshire, Vermont, Massachuset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This study concluded by reflecting on the paradox of a system that, by using a managerial approach that mainly pursues efficiency, generates lack of trust on the part of the staff towards the managerial system itself (Albsoul, FitzGerald, Finucane, & Borkoles, 2019). A crucial role, in this constant tension between organisational efficiency and meeting patients' needs, is played by the charge nurse and the nursing leaders, who constantly have to balance resources to obtain positive outcomes to achieve the effectiveness and efficiency of nursing interventions (Ingwell‐Spolan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study concluded by reflecting on the paradox of a system that, by using a managerial approach that mainly pursues efficiency, generates lack of trust on the part of the staff towards the managerial system itself (Albsoul, FitzGerald, Finucane, & Borkoles, 2019). A crucial role, in this constant tension between organisational efficiency and meeting patients' needs, is played by the charge nurse and the nursing leaders, who constantly have to balance resources to obtain positive outcomes to achieve the effectiveness and efficiency of nursing interventions (Ingwell‐Spolan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The context is virtually paradoxical: Nurses are required to provide patient‐centred care within a productive and standardised system . Hence, a tension between productivity and nurse's satisfaction can take place . This suggests the need for ongoing support for nursing staff from nursing management and increased attention for their challenges in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…66 Hence, a tension between productivity and nurse's satisfaction can take place. 67 This suggests the need for ongoing support for nursing staff from nursing management and increased attention for their challenges in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…This needed nurses who were motivated to do their work and because the challenge is still continuing, it is imperative that nurses be continuously motivated. According to (2), it was revealed that a nurse manager should advocate for both the patient and the nurses to promote quality care.…”
Section: Introductionmentioning
confidence: 99%